COVID‐19 and ischemic stroke. (17th July 2021) - Sagris, Dimitrios; Papanikolaou, Aikaterini; Kvernland, Alexandra; Korompoki, Eleni; Frontera, Jennifer A.; Troxel, Andrea B.; Gavriatopoulou, Maria; Milionis, Haralampos; Lip, Gregory Y. H.; Michel, Patrik; Yaghi, Shadi; Ntaios, George
Abstract: Since the onset of the COVID‐19 pandemic, a substantial proportion of COVID‐19 patients had documented thrombotic complications and ischemic stroke. Several mechanisms related to immune‐mediated thrombosis, the renin angiotensin system and the effect of SARS‐CoV‐2 in cardiac and brain tissue may contribute to the pathogenesis of ischemic stroke in patients with COVID‐19. Simultaneously, significant strains on global healthcare delivery, including ischemic stroke management, have made treatment of stroke in the setting of COVID‐19 particularly challenging. In this review, we summarize the current knowledge on epidemiology, clinical manifestation, and pathophysiology of ischemic stroke in patients with COVID‐19 to bridge the gap from bench to bedside and clinical practice during the most challenging global health crisis of the last decades. Abstract : Ischemic stroke among COVID‐19 patients correlates with increased disability and mortality. Hypercoagulopathy, angiotensin‐converting enzyme 2 inhibition, and cardioembolism are potential stroke mechanisms in COVID‐19. SARS‐CoV‐2–specific vaccinations and immunomodulatory agents may affect stroke prevention and treatment in COVID‐19 patients.